Case report: progression of pre-septal cellulitis to orbital subperiosteal abscess despite intravenous broad-spectrum antibiotics in a child - Noor Aniah Azmi; Norshamsiah MD; Bastion, Mae-Lynn Catherine; Safinaz Mohd Khialdin; Mawaddah Azman (Faculty of Medicine, UKM Medical Centre, 2016)
We report a case of a 7-year-old girl who initially presented with painless right eyelid swelling with full extra-ocular movement (EOM). She was treated with intravenous broad-spectrum antibiotics for preseptal cellulitis but her condition worsened. An urgent magnetic resonance imaging (MRI) of the brain and orbit showed orbital abscess, subperiosteal abscess in the medial orbital wall and evidence of sinusitis in the anterior ethmoidal air cells. She underwent Endoscopic Orbital Decompression (EOD) surgery on day 4 of presentation and her condition improved remarkably. We report a case of orbital abscess with subperiosteal abscess in the medial orbital wall. This case highlights the possibility of progression of orbital cellulitis despite administration of a broad-spectrum antibiotic.